Pengaruh Industri Pt. Pupuk Kaltim Tbk Terhadap Laju Pertumbuhan Karang Massive Di Perairan Bontang Kuala, Kota Bontang, Kalimantan Timur - Supriharyono, Supriharyono (Master Program of Environmental Health, Faculty of Public Health, Diponegoro University, 2004)
ABSTRACK Growth rates ( linear skeletal extension) and the timing of skeletal band formation were measured in eight specimens of the messive coral Porites Iutea at three sites (BK1, BK2, and BK3) and three depths, i.e. 1 m, 3 m, and 5 m in each site. The sites were located in Bontang Kuala Regency, located about 7.5 km from the fertilizing industry, PT. Pupuk Kaltim Tbk, Bontang. Growth rates were measured using two techniques, i.e. X-radiograph and UV-light. Result of the study indicates that the timing of the high density (HD) and low density (LD) bands is synchronous at the three locations. A one year growth is characterized by three HD bands, one of which is usually very dense. Illumination of the coral slabs by UV-light revealed a distinct fluorescent banding pattern on all coral specimens. The data indicatethat the fluorescent bands are usually associated with the high density bands which are accreted during the wet season period. It is characterized by the high of land run-off containing elevated concentrations of fulvic and humic acid compounds, and this apparently occurred almost through out the year. Comparisons of the skeletal extension rates indicate that the growth rates of P. Iutea are not significantly difference (p <0.05) euther between sites or depths. The average of coral growth rates ranged from 0.8-1.2 cm/year. However, the annual growth rate tends to be fluctuated. Likely it is varied with the amount of rainfall (p < 0.01), but it is no affected by the number of urea production (dust), fertilizing industry, PT. Pupuk Kaltim Tbk. Â Key Word : Coral growth rate, characterize of massive coralâ€™s growth